HIV Infection and the Risk of World Health Organization–Defined Sudden Cardiac Death - Matthew S. Freiberg (Wiley, 2021)
Background People living with HIV have higher sudden cardiac death (SCD) rates compared with the general population. Whether HIV infection is an independent SCD risk factor is unclear. Methods and Results This study evaluated participants from the Veterans Aging Cohort Study, an observational, longitudinal cohort of veterans with and without HIV infection matched 1:2 on age, sex, race/ethnicity, and clinical site. Baseline for this study was a participant's first clinical visit on or after April 1, 2003. Participants were followed through December 31, 2014. Using Cox proportional hazards regression, we assessed whether HIV infection, CD4 cell counts, and/or HIV viral load were associated with World Health Organization (WHO)–defined SCD risk. Among 144 336 participants (30% people living with HIV), the mean (SD) baseline age was 50.0 years (10.6 years), 97% were men, and 47% were of Black race. During follow‐up (median, 9.0 years), 3035 SCDs occurred. HIV infection was associated with increased SCD risk (hazard ratio [HR], 1.14; 95% CI, 1.04–1.25), adjusting for possible confounders. In analyses with time‐varying CD4 and HIV viral load, people living with HIV with CD4 counts <200 cells/mm3 (HR, 1.57; 95% CI, 1.28–1.92) or viral load >500 copies/mL (HR, 1.70; 95% CI, 1.46–1.98) had increased SCD risk versus veterans without HIV. In contrast, people living with HIV who had CD4 cell counts >500 cells/mm3 (HR, 1.03; 95% CI, 0.90–1.18) or HIV viral load <500 copies/mL (HR, 0.97; 95% CI, 0.87–1.09) were not at increased SCD risk. Conclusions HIV infection is associated with increased risk of WHO‐defined SCD among those with elevated HIV viral load or low CD4 cell counts.